2011
DOI: 10.1111/j.1365-2265.2011.04185.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of gonadotrophin suppression in girls treated with GnRH analogue for central precocious puberty; validity of single luteinizing hormone measurement after leuprolide acetate injection

Abstract: Single LH determination 90 min after GnRHa administration using a cut-off level of 2·5 mIU/ml reflects pubertal suppression with a high sensitivity and specificity. However, this test may fail to show pubertal suppression in some cases. Those patients who appear to be inadequately suppressed should be reassessed using standard iv GnRH stimulation test for optimal dose adjustment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 22 publications
(77 reference statements)
3
16
0
2
Order By: Relevance
“…Our finding of undetectable serum estradiol levels after depot GnRHa is stronger evidence for adequate pubertal suppression. We also observed that gonadotropins and estradiol responses to depot triptorelin did not change significantly along 2 years of treatment, while previous studies only performed a unique evaluation at 3 months of treatment [13,15]. …”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Our finding of undetectable serum estradiol levels after depot GnRHa is stronger evidence for adequate pubertal suppression. We also observed that gonadotropins and estradiol responses to depot triptorelin did not change significantly along 2 years of treatment, while previous studies only performed a unique evaluation at 3 months of treatment [13,15]. …”
Section: Discussionmentioning
confidence: 56%
“…They showed great variation, from 2.5 to 6.6 IU/l. We consider our LH-3h cutoff is not strictly comparable with them because of differences in the design of the study, the sampling time and LH assays [6] and because of the use of depot leuprolide, a different GnRHa with respect to our study [13,14,15]. Even more, these previous studies have not included the assessment of E 2 -24h in order to determine that steroidogenesis is suppressed.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…GnRHa therapy (Leuprolide acetate) was administered at 3.75 mg every 4 weeks; the dose had to be increased to 7.5 mg in three children (cases 5, 8, 10) who had a higher LH response to GnRHa of more than 2.5 IU, 90 minutes after injections. 16 Therapy was stopped in eight patients (nos. 1, 3, 5, 6, 8, 9, 10 and 11) due to advanced bone age during the last visit.…”
Section: Therapy and Follow-upmentioning
confidence: 99%
“…Given these limitations, GnRH-stimulated gonadotropin measurements are commonly used to rule out EP. However, there is a significant overlap of peak LH levels between prepubertal and early pubertal values in normal children (5,23). In studies assessing children with signs of EP, a peak LH value of ≥5 IU/L was found to have a sensitivity of only 78% in predicting subsequent pubertal progression (23).…”
Section: Discussionmentioning
confidence: 99%